New Materials and Advanced Procedures of Obtaining and Processing - Sandu, Andrei Victor (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this Special Issue is to highlight the most recent advancements in the field of materials science, showcasing novel techniques that can be used in a variety of applications, including medical and civil engineering. This collection of research articles was edited by Assoc. Prof. Andrei Victor Sandu from the Gheorghe Asachi Technical University of laşi, Romania.